2018
DOI: 10.3389/fimmu.2018.02256
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Association of Pulmonary Surfactant Protein Genes, SFTPA1, SFTPA2, SFTPB, SFTPC, and SFTPD With Cystic Fibrosis

Abstract: Surfactant proteins (SP) are involved in surfactant function and innate immunity in the human lung. Both lung function and innate immunity are altered in CF, and altered SP levels and genetic association are observed in Cystic Fibrosis (CF). We hypothesized that single nucleotide polymorphisms (SNPs) within the SP genes associate with CF or severity subgroups, either through single SNP or via SNP-SNP interactions between two SNPs of a given gene (intragenic) and/or between two genes (intergenic). We genotyped … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
67
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 156 publications
0
67
2
Order By: Relevance
“…The SNPs, rs1124 and rs4715, are exonic splicing enhancers, while rs8192309, rs8192313, rs13248346, rs2070686 and rs4995702 are all transcription factor binding sites, as predicted using the SNPinfo method, as previously reported ( 31 ) ( Table SI ). It has also been reported that the rs4715 SNP was associated with respiratory distress syndrome ( 5 , 14 , 16 ); however, this was not identified in the present study. The results also suggested that the SNP rs1124 may serve an important role in disease development, which was in accordance with the results of previous studies ( 5 , 13 , 14 , 16 ).…”
Section: Discussioncontrasting
confidence: 84%
See 4 more Smart Citations
“…The SNPs, rs1124 and rs4715, are exonic splicing enhancers, while rs8192309, rs8192313, rs13248346, rs2070686 and rs4995702 are all transcription factor binding sites, as predicted using the SNPinfo method, as previously reported ( 31 ) ( Table SI ). It has also been reported that the rs4715 SNP was associated with respiratory distress syndrome ( 5 , 14 , 16 ); however, this was not identified in the present study. The results also suggested that the SNP rs1124 may serve an important role in disease development, which was in accordance with the results of previous studies ( 5 , 13 , 14 , 16 ).…”
Section: Discussioncontrasting
confidence: 84%
“…It has also been reported that the rs4715 SNP was associated with respiratory distress syndrome ( 5 , 14 , 16 ); however, this was not identified in the present study. The results also suggested that the SNP rs1124 may serve an important role in disease development, which was in accordance with the results of previous studies ( 5 , 13 , 14 , 16 ). The SNPs, rs4715 and rs1124, are both missense, in which the amino acids 138 (Thr/Asn) and 186 (Ser/Asn) are changed, respectively; however, the potential mechanisms in which they affect function remain unknown.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations